COOPERATIVE RESEARCH IN COST-PRICE RELATIONSHIPS. - Dean, Joel (The Accounting Review, 1939)
This article focuses on research in cost-price relationships. In forwarding research in the field of cost-price relationships it is necessary first to determine what studies are most important from the standpoint of their practical usefulness to business and their significance to the science of economics. As hypotheses in studying cost-price relationships the recently developed neo- classical theoretical analysis of imperfect competition has been used as a means of organizing research problems, and bringing into sharp contrast the viewpoint of the theorist and the business man. Cost concepts are too restricted for many practical purposes. Marginal cost, for example, must for some purposes be expanded to a concept of opportunity costs of several alternatives, such as shutting down, selling other products, etc. Under conditions of multiple production, moreover, necessarily arbitrary allocations of some cost items make it difficult to determine costs of individual products. A realistic concept of price must be complex because pricing practices differ from firm to firm and industry to industry.